2017
DOI: 10.1159/000479477
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy and Liver Function in ALPPS: Correlation with Morbidity and Mortality

Abstract: Background: ALPPS (associating liver partition and portal vein ligation for staged hepatectomy) was introduced with the promise to reduce posthepatectomy liver failure (PHLF) in extended hepatectomies but has higher morbidity and mortality rates compared to conventional methods of volume enhancement. There are few studies of the incidence of PHLF after ALPPS and little information on how to avoid PHLF by functional testing. It remains unclear what causes the compromise in liver function despite rapid volume ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Although ALPPS forces more hepatocytes into proliferation, causing significantly greater volumetric regeneration of the FLR, recent studies have reported significantly lagging functional recovery. As the maintenance of liver function is highly energy‐dependent, hepatocyte bioenergy impairment presumably underlies this slower functional regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ALPPS forces more hepatocytes into proliferation, causing significantly greater volumetric regeneration of the FLR, recent studies have reported significantly lagging functional recovery. As the maintenance of liver function is highly energy‐dependent, hepatocyte bioenergy impairment presumably underlies this slower functional regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ALPPS-induced accelerated weight gain is not the manifestation of passive congestion or oedema; it is indicative of cellular proliferation, consistent with the clinical findings of Eshmuminov and colleagues 22 . Although ALPPS forces more hepatocytes into proliferation, causing significantly greater volumetric regeneration of the FLR, recent studies 23,24 have reported significantly lagging functional recovery. As the maintenance of liver function is highly energy-dependent, hepatocyte bioenergy impairment presumably underlies this slower functional regeneration.…”
Section: Mitochondrial Morphology Changes Significantly After Alppsmentioning
confidence: 99%
“…[13][14][15][16] The "disproportionate" increase of the remnant liver volume compared to fRLF might be the cause of the greater morbidity and mortality reported in ALPPS. 7 In addition, recent pathologic studies of the remnant liver showing a higher density but smaller hepatocytes in the remnant liver seem to support the dysfunctional vol-ume theory. These hepatocytes also contain fewer organelles and are thus less metabolic active.…”
Section: Article In Pressmentioning
confidence: 84%
“…[3][4][5][6] Individually, the standard analysis of these preoperative assessments have shown shortcomings in predicting PHLF in the interstage of ALPPS. [7][8][9][10] But, by using the results in combination, we suggest a new integrated parameter: the relative proportion kinetic growth rate (KGR) fraction of functional over volume increase that might prove to be better at predicting PHLF at the interstage of ALPPS.…”
Section: Article In Pressmentioning
confidence: 99%
“…These recounts may provide us with hints for overcoming the unresolved challenges. Additionally, we asked an expert radiologist of PVE as well as two driving forces of the ALPPS procedure in the world to contribute articles on the state-of-the-art technique of PVE to obtain an optimal hypertrophy of the liver [3], on the relationship between hypertrophy and liver function in ALPPS [4], and on the pitfalls in PVE and ALPPS [5]. Moreover, since the modalities of assessing the functional reserve of the liver differ between Western and Eastern countries, we asked two experts in the field from each area to delineate the currently most reliable methods [6,7].…”
mentioning
confidence: 99%